HEAD LICE IN SCHOOL CHILDREN IN UBERLANDIA, MINAS GERAIS STATE, BRAZIL - G. Mendes, Gabriela; Borges-Moroni, Raquel; T. Moroni, Fábio; Mendes, Júlio (Revista de Patologia Tropical / Journal of Tropical Pathology, 2017)
School-aged children have shown to be the group most susceptible to Pediculus capitis infestation, possibly due to their habits and behaviors. The purpose of the study was to verify the prevalence of head pediculosis in preschool children from Uberlândia, MG, and factors associated with infestation. The children’s parents or guardians were also evaluated regarding socioeconomic status, knowledge of symptomatology and control of this ectoparasitosis. Data were obtained by direct examination of each child’s head and a questionnaire answered by parents/guardians. The overall prevalence rate was 7.5% among the 372 children examined, and 4 to 5-year-old girls with long hair presented significantly higher prevalence rates. Information from the questionnaires indicated that 45% of the children had already been infested at least once and the main symptom mentioned was intense itching on the scalp. Those responsible mostly used natural control measures to control infestations. The results indicated that children under the age of six should also be included in head pediculosis control programs.